Refactoring C with conditional compilation - Garrido, Alejandra (2003)
Refactoring, an important technique for increasing flexibility of the source code, can be applied with much ease and efficiency by using automated tools. There is currently a lack of refactoring tools for C with full support for preprocessor directives because directives complicate refactorings in many ways. This paper describes refactoring of C programs in the presence of conditional compilation directives and how we propose to support them in a refactoring tool.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 22/12/2008)
18th IEEE International Conference on Automated Software Engineering (ASE’2003), October 2003.
Keywords: MULTIPROCESADORES; MATEMÁTICA DE LA COMPUTACIÓN; TURBO PASCAL